Communication Latency in Multi-agent System for Microgrid - Singh, N. (Institute of Electrical and Electronics Engineers Inc., 2019)
This paper discusses about designing a multiagent system (MAS) for the IEEE bus-4 microgrid. The design models the communication latency among various agents. These intelligent agents are arranged as per the distributed manner impacting the higher-level capabilities of the microgrid. This helps in the controlling and maintaining coordination between power and communication network of the microgrid. Communication latency or delay is divided into system and communication delay. The simulation of the methodology is conducted to identify the delay at each segment of the microgrid, i.e. generation, transmission, distribution and load. The model is simulated using a multi-agent simulator i.e. AnyLogic. Which has the interest to measure how fast system is responding based on the installation of MAS for IEEE bus-4. Â© 2019 IEEE.